(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Hepatocellular carcinoma is one of the leading causes of cancer-related mortality in Vietnam. Transarterial chemoembolization (TACE) is the standard treatment for patients with intermediate-stage disease or those ineligible for curative therapies. Objective: To evaluate the effectiveness and safety of TACE in the treatment of hepatocellular carcinoma at the Viet Nam – Cuba Dong Hoi Friendship Hospital. Materials and methods: A prospective descriptive and analytical study was conducted on 50 patients with hepatocellular carcinoma treated with TACE between March 2020 and December 2024. Treatment response was assessed using the mRECIST criteria, and prognostic factors were analyzed using logistic regression. Results: TACE achieved a high treatment response rate, with an increasing proportion of complete response over time. Tumor size < 5 cm was an independent predictor of early response, while solitary tumors were strongly associated with favorable mid-term response. No major complications or procedure-related mortality were recorded.